2012
DOI: 10.3758/s13421-012-0197-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in autobiographical narratives: He shoots and scores; she evaluates and interprets

Abstract: Research on autobiographical narratives consistently demonstrates that whereas women's narratives emphasize evaluative information, men's narratives are factually oriented. These narrative differences might reflect gender differences in either the autobiographical knowledge base or the way information from the knowledge base is selected when a narrative is constructed. The present experiment evaluated these two (potentially complementary) hypotheses by assessing memory soon after an event and after a period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…Middle Eastern women rated their events as more specific and generated longer narratives compared with Middle Eastern men in both time orientations. This is in accordance with previous studies showing stylistic differences in narration of memories with women telling and writing longer narratives than men (Fivush et al, 2011;Schulkind, Schoppel, & Scheiderer, 2012). Also it supports studies showing that women tend to generate longer, more detailed and more specific narratives of personal events (Hayne & MacDonald, 2003;Herlitz & Rehnman, 2008;Pillemer, Wink, DiDonato, & Sanborn, 2003;Ross & Holmberg, 1990;Wang et al, 2011).…”
Section: Effects Of Gendersupporting
confidence: 92%
“…Middle Eastern women rated their events as more specific and generated longer narratives compared with Middle Eastern men in both time orientations. This is in accordance with previous studies showing stylistic differences in narration of memories with women telling and writing longer narratives than men (Fivush et al, 2011;Schulkind, Schoppel, & Scheiderer, 2012). Also it supports studies showing that women tend to generate longer, more detailed and more specific narratives of personal events (Hayne & MacDonald, 2003;Herlitz & Rehnman, 2008;Pillemer, Wink, DiDonato, & Sanborn, 2003;Ross & Holmberg, 1990;Wang et al, 2011).…”
Section: Effects Of Gendersupporting
confidence: 92%
“…Some evidence indicates that the right hemisphere is biased toward processing the “gist” of memories, whereas the left hemisphere is biased toward finer detailed processing [ 35 , 36 ]. This, however, it not uniformly supported, as, although females recall longer, richer, and more evaluative narratives for autobiographical memories, males have been shown to recall more factual information [ 37 ]. Particularly with regard to autobiographic memories, parent–child reminiscence practices may partially explain the observed sex differences, as mothers tend to reminisce more elaborately and discuss emotional events in greater detail with their daughters when compared to their sons [ 38 ].…”
Section: Potential Psychological Explanations For Sex Differences mentioning
confidence: 99%
“…In contrast, we found that reliance on cognitive processing words differed by sex in ASD, such that cognitive process word production was significantly reduced in autistic males only . Diminished internal state language, including cognitive process words, has been interpreted as reflecting Theory of Mind impairments in ASD [9, 59], but prior studies rarely included sufficient numbers of girls to assess whether typical sex differences in social cognition [23, 93] and narratives [77, 97] persist in autistic boys and girls separately. Our finding, that cognitive process word deficits during storytelling are largely specific to males with ASD, suggests that historical reliance on predominantly male samples may have led to generalizations about narration in ASD that do not apply to girls (although this study still includes a smaller sample of girls than boys, and warrants replication).…”
Section: Discussionmentioning
confidence: 99%
“…Parental narratives directed at girls include more references to emotions and internal states than narratives directed toward boys [43]. Subsequently, girls tell narratives that are distinct from boys’ narratives [12, 17, 67], including longer narratives that are more emotionally laden and more likely to reference others’ internal states [77, 97]. However, it is largely unknown whether the narratives of boys and girls with ASD also differ from one another.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation